Quercetin Promote the Chemosensitivity in Organoids Derived from Patients with Breast Cancer - Meng S; Cao Y; Lu L; Li X; Sun S; Jiang F; Lu J; Fan D; Han X; Yao T (Breast Cancer: Targets and Therapy)
Shengwen Meng,1 Yifan Cao,1 Lei Lu,1 Xuanhe Li,1 Siyu Sun,1 Fangqian Jiang,1 Jianfei Lu,2 Dongwei Fan,3 Xinxin Han,1 Tingjing Yao1 1Department of Surgical Oncology, The Fourth Ward of Breast and Thyroid, the First Affiliated Hospital of Bengbu Medical College, Bengbu, Anhui Province, People’s Republic of China; 2Department of Breast and Thyroid Surgery, Bengbu First People’s Hospital, Bengbu, Anhui Province, People’s Republic of China; 3Department of General Surgery, Affiliated Hospital of West Anhui Health Vocational College, Luan, Anhui Province, People’s Republic of ChinaCorrespondence: Tingjing Yao, Department of Surgical Oncology, The Fourth Ward of Breast and Thyroid, The First Affiliated Hospital of Bengbu Medical College, 287 Changhuai Road of Bengbu, Anhui Province, 233099, People’s Republic of China, Email 13855200468@163.comAim: The study aimed to culture organoids from tissues of patients with breast cancer (BC) and use the organoids to measure the sensitivity to quercetin and its combination with chemotherapeutic agents.Methods: Four patient-derived organoids (PDOs) of BC were cultured. The proliferative activity and morphology of PDOs were evaluated on different generations and after resuscitation. H&E and immunohistochemical (IHC) staining were used to identify the pathological changes and the expression of biomarkers. The sensitivity to quercetin and chemotherapeutic agents and their combinations were evaluated using adenosine triphosphate (ATP) viability assays.Results: We successfully obtained all PDOs from BC tissues. PDOs preserved their activity and morphology during generation passage. In addition, the pathological changes and expression patterns of estrogen receptor (ER), human epidermal growth factor receptor (HER2), and Ki67 of each PDO were consistent with their original tissues. All four PDOs were highly sensitive to quercetin, and their IC50 values were less than 22 μM. PDOs showed better sensitivity to docetaxel and epirubicin hydrochloride, but less sensitivity to cis-platinum. Combination with quercetin promoted the sensitivity to three chemotherapeutic agents. In particular, the IC50 value of cis-platinum greatly decreased.Conclusion: We successfully established PDOs from patients with BC and demonstrated that quercetin can promote the sensitivity of chemotherapeutic agents in these PDOs.Keywords: quercetin, breast cancer, patient-derived organoids, drug sensitivity